Dynamic nature of active chromatin hubs - Gavrilov, A.A.; Philonenko, E.S.; Iarovaia, O.V.; Razin, S.V. (Вiopolymers and Cell, 2011)
Aim. In order to get more information about organization of active chromatin hubs and their role in the regulation of gene transcription we have studied the spatial organization of the a-globin gene domain in cultured chicken erythroblasts. Methods. The chromosome conformation capture (3C) protocol was employed to analyze the 3D configuration of the chicken a-globin gene domain. Results. We have demonstrated that in the same cell population the chicken domain of a-globin gene may be organized in two different active chromatin hubs. One of them appears essential for the activation of the a-globin gene expression while the other – for the activation of TMEM8 gene which constitutes a part of the a-globin gene domain in chicken, but not in human and other mammals. Importantly, two regulatory elements participate in the formation of both active chromatin hubs. Conclusions. The assembly of the same genomic area into two alternative chromatin hubs which share some regulatory elements suggests that active chromatin hubs are dynamic rather than static, and that regulatory elements may shuttle between different chromatin hubs. Keywords: active chromatin hub, globin gene, genomic domain, chromosome conformation capture. Мета. Щоб отримати нову інформацію стосовно організації активаторних хроматинових блоків та їхньої ролі в регуляції транскрипції ми вивчили просторову організацію домену a-глобінових генів у культивованих курячих еритробластах. Методи. Для анализу 3D конфігурації домену a-глобінових генів використано метод фіксації конформації хромосоми (3С). Результати. Ми продемонстрували, що в одній і тій самій популяції курячих клітин домен a-глобінових генів може бути організованим у два різних хроматинових блоки. Один з них необхідний для активації транскрипції a-глобінових генів, тоді як другий забезпечує активацію транскрипції гена TMEM8. Цей ген входить до складу домену aглобінових генів курей, але не ссавців і людини. Важливо, що два регуляторних елементи домену a-глобінових генів присутні у складі обох активаторних хроматинових блоків. Висновки. Існування в одному й тому ж геномному домені двох різних активаторних комплексів, які мають у своєму складі спільні регуляторні елементи, свідчить про динамічну природу активаторних хроматинових блоків, що дозволяє спільним регуляторним елементам періодично переміщуватися з одного комплексу в другий. Ключові слова: активаторні хроматинові блоки, глобіновий ген, геномний домен, метод фіксації хромосоми. Цель. Чтобы получить новую информацию об организации активаторных хроматиновых блоков и их роли в регуляции транскрипции, мы изучили пространственную организацию домена a-глобиновых генов в культивируемых куриных эритробластах. Методы. Для анализа 3D конфигурации домена a-глобиновых генов использован метод фиксации конформации хромосомы (3С). Результаты. Мы продемонстрировали, что в одной и той же популяции куриных клеток домен a-глобиновых генов может быть организован в два различных хроматиновых блока. Один из них необходим для активации транскрипции a-глобиновых генов, в то время как другой обеспечивает активацию транскрипции гена TMEM8. Этот ген входит в состав домена a-глобиновых генов кур, но не млекопитающих и человека. Важно, что два регуляторных элемента домена a-глобиновых генов присутствуют в составе обоих активаторных хроматиновых блоков. Выводы. Существование в одном и том же геномном домене двух разных активаторных комплексов, имеющих в своем составе общие регуляторные элементы, свидетельствует о динамической природе активаторных хроматиновых блоков, что позволяет общим регуляторным элементам периодически перемещаться из одного комплекса в другой. Ключевые слова: активаторные хроматиновые блоки, глобиновый ген, геномный домен, метод фиксации хромосомы.